Biohydrogen generation: Concepts and applications on brazilian agro-industrial wastewaters - Rodrigues, Caroline V. [UNESP]; Santana, Kamili O. [UNESP]; Pires, Lorena O. [UNESP]; Brienzo, Michel [UNESP]; Maintinguer, Sandra I. [UNESP] (My University, 2017)
Some agro-industries activities, such as biodiesel, ethanol, citrus, and cassava production represent a significant share of the Brazilian economy. Associated with these productions, large amounts of wastewater are generated from these processes, representing a serious environmental risk. The waste conversion into energy, such as hydrogen, is considered a promising alternative to overcome organic waste accumulation. Cassava is a native plant from South America and it can be used to produce starch and flour and both processes generate solid and liquid wastes with bioenergy potential. The bagasse produced during the starch process can be used as a substrate by anaerobic microorganisms for the production of value added products, such as organic acids and ethanol, for example. The starch process generates a kind of wastewater that is rich in organic matter however, its discharge in a water body without pretreatment causes a serious drop in the oxygen levels, representing a polluting potential that can be a dramatic threat to the local fauna. Thus, the anaerobic treatment is the most convenient option for this waste, making these substrates suitable for hydrogen production. Besides that, millions of tons of orange biomass are generated per year due to the production of orange juice. Therefore, citrus waste can also be used for biofuel production. Significant amounts of vinasse are generated from the production of second-generation ethanol from citrus bagasse. Vinasse is a wastewater that contains large amounts of organic matter and nutrients, but it needs to be pretreated before being discarded due to the harmful impact it can have in the environment. Thus, the promising use of the vinasse consists of hydrogen generation through dark fermentation process. Biodiesel can be produced from virgin vegetable oils or from used cooking oil. In both cases, high concentrations of crude glycerol are generated as co-product (about 10kg of glycerol per each 100 kg of biodiesel produced). Some Brazilian government programs encourage biodiesel production. Thereby, Brazil stands out for being the country which is most responsible for the current production of this biofuel in the global context. However, glycerol has been becoming an environmental tendency, what compromises the sustainability of the biodiesel process. In this scenario, the agro-industrial products that have a significant productivity are the ones that generate more wastewaters. Therefore, this chapter will contribute with a theoretical view about the biologic processes of hydrogen production and their application on researches that have been done about the H2-generation at low costs which, at the same time, promote these wastes degradation, combining agroindustrial growth with sustainable practices for clean energy generation.
Keywords: Anaerobic digestion; Biodiesel; Cassava; Citrus; Crude glycerol; Vinasse